Change in local conformation of polymer chains at film surface attached to solid surface. Issue 17 (13th April 2022) - Harada, Rei; Kawaguchi, Daisuke; Yamamoto, Satoru; Tanaka, Keiji
Abstract : The conformational relaxation of polystyrene in response to the change in the contact medium from the air to the solid was discussed by sum-frequency generation spectroscopy and molecular dynamics (MD) simulation. Abstract : Adhesion is a molecular event where polymer chains contact with a material surface to form an interfacial layer. To obtain a better understanding of the adhesion on a molecular scale, we herein examined the conformational change of polystyrene (PS) chains at the film surface after contacting with hydrophobic or hydrophilic surfaces using sum-frequency generation (SFG) spectroscopy. Chains altered their local conformations with a quartz surface more quickly than a hydrophobic alkyl-functionalized one. A full-atomistic molecular dynamics simulation showed that these results, which were coupled with the contact process of PS chains with the solid surface, could be explained in terms of the Coulomb interaction between them.